Serviços ecossistêmicos do reservatório da UHE Carlos Botelho (Lobo-Broa): uma nova abordagem para o gerenciamento e planejamento dos múltiplos usos de represas - Periotto, Natalia Andricioli (Universidade Federal de São Carlos, 2011)
Reservoirs of hydroelectric power generation plants are of strategic importance due to its multiple uses as generation of clean energy, water supply, and other social economic opportunities since the beginning of construction, which may also cause negative impacts. Assessing ecosystem services is an approach to complement Environmental Impact Assessment and a tool for cost-effectiveness analysis. This study identified 20 ecosystem services of Carlos Botelho (Lobo-Broa) hydroelectric power plant reservoir (Itirapina, São Paulo, Brazil) and its upstream wetlands, from Itaqueri River and Lobo Stream. It has also assigned qualitative and quantitative values for these services and analyzed their drivers of change. Qualitative valuation indicated direct and indirect influence of ecosystem services on human well-being. Preliminary quantitative valuation resulted in USD 120,445,657.87.ha-1 or USD 45,623.35.ha- 1.year-1, highlighting that losses on indirect use ecosystem services, as groundwater recharge, may reflect on local and regional economy. Analysis of drivers indicated that adequate and efficient environmental management along Tietê-Jacaré hydrographic basin, especially concerning the recovery of spatial heterogeneity, is necessary to avoid ecosystem services losses, especially tourism and recreation that provide local economic fluxes and human well-being.
Keywords: Ecologia; Serviços do ecossistema; Usinas hidrelétricas; Água - gerenciamento; Forçantes (drivers); Bacias hidrográficas; Reservoirs; Hydroelectric power generation plant; Wetlands; Ecosystem services; Hydrographic basin; CIENCIAS BIOLOGICAS::ECOLOGIA